a.\(x^2\left(x+1\right)+2x\left(x+1\right)=0\)
\(\left(x^2+2x\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x^2+2x=0\\x+1=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x\left(x+2\right)=0\\x=-1\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=0\\x+2=0\\x=-1\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=0\\x=-2\\x=-1\end{matrix}\right.\)
Vậy \(x=0;x=-2\) hoặc \(x=-1\) .
b.\(\dfrac{4}{9}-25x^2=0\)
\(\left(\dfrac{2}{3}\right)^2-\left(5x\right)^2=0\)
\(\left(\dfrac{2}{3}-5x\right)\left(\dfrac{2}{3}+5x\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}\dfrac{2}{3}-5x=0\\\dfrac{2}{3}+5x=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}5x=\dfrac{2}{3}\\5x=-\dfrac{2}{3}\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{2}{15}\\x=-\dfrac{2}{15}\end{matrix}\right.\)
Vậy \(x=\dfrac{2}{15}\) hoặc \(x=-\dfrac{2}{15}\) .